2019
DOI: 10.3389/fncel.2019.00127
|View full text |Cite
|
Sign up to set email alerts
|

The Role of High Mobility Group Box 1 in Ischemic Stroke

Abstract: High-mobility group box 1 protein (HMGB1) is a novel, cytokine-like, and ubiquitous, highly conserved, nuclear protein that can be actively secreted by microglia or passively released by necrotic neurons. Ischemic stroke is a leading cause of death and disability worldwide, and the outcome is dependent on the amount of hypoxia-related neuronal death in the cerebral ischemic region. Acting as an endogenous danger-associated molecular pattern (DAMP) protein, HMGB1 mediates cerebral inflammation and brain injury … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
58
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(59 citation statements)
references
References 117 publications
(165 reference statements)
1
58
0
Order By: Relevance
“…The results of studies on IS suggest the important role of HMGB1 in stroke-induced immunosuppression, which is similar to a phenomenon observed in SAH [28][29][30][31]. The levels of this protein were increased in IS patients and correlated with the number of circulating leukocytes, stroke severity, and inflammatory markers [32].…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…The results of studies on IS suggest the important role of HMGB1 in stroke-induced immunosuppression, which is similar to a phenomenon observed in SAH [28][29][30][31]. The levels of this protein were increased in IS patients and correlated with the number of circulating leukocytes, stroke severity, and inflammatory markers [32].…”
Section: Discussionsupporting
confidence: 66%
“…RNAs were isolated from peripheral blood cells, whereas protein was measured in plasma. Circulating HMGB1 can be released from various cells, including activated platelets [31,37]. The activation of platelets is a known phenomenon in SAH and is associated with early brain injury after SAH [3,38].…”
Section: Discussionmentioning
confidence: 99%
“…There has been an ongoing research finding connections between HMGB1 and immunopathology of disorders and traumas in various body systems. Its role in ischemic stroke was described by Ye et al [16]. Its complex function in cardiomyocyte senescence and cardiac inflammatory injury was described by Lu et al [17].…”
Section: Introductionmentioning
confidence: 98%
“…Both experimental and clinical studies indicate that HMGB1 is released from injured brain tissues as well as activated microglia within the ischemic tissues and activates an early inflammatory response after AIS [109]. HMGB1signals via TLR2 and TLR4 signaling activate the NF-κB pathway and induce a proinflammatory response [110]. Several studies have shown that plasma levels of HMGB1 increase in ischemic stroke and correlate with poor outcome [111][112][113].…”
Section: Tlr9mentioning
confidence: 99%